Pengaruh Orientasi Etika, Retaliasi, Komitmen Profesional dan Sosialisasi Antisipatif Mahasiswa Akuntansi terhadap Intensi Whistleblowing - Susanti, Rini; Fauzihardani, Eka (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to clarify the influence of factors such as ethical idealism orientation, retaliation, professional commitment, and anticipatory socialization on the intention to whistleblowung. The research uses a quantitative approach. The sampling method employed in this study is non probability sampling, with purposive sampling as the technique. The sample consists of active undergraduate accounting students who have completed the Business Ethics and Accounting Profession courses. The number of respondents was determined using the Krejcie and Morgan method, resulting in a sample size of 260 individuals. The findings of this study reveal that: (1) Ethical idealism orientation has a positive influence on accounting students' intention to whistleblowing; (2) Retaliation does not have a significant influence on accounting students' intention to whistleblowing; (3) Professional commitment does not have a significant influence on accounting students' intention to whistleblowing; (4) Anticipatory socialization does not have a significant influence on accounting students' intention to whistleblowinging.